Initial Carbon–Carbon Bond Formation during the Early Stages of the Methanol‐to‐Olefin Process Proven by Zeolite‐Trapped Acetate and Methyl Acetate. (2nd November 2016) - Chowdhury, Abhishek Dutta; Houben, Klaartje; Whiting, Gareth T.; Mokhtar, Mohamed; Asiri, Abdullah M.; Al‐Thabaiti, Shaeel A.; Basahel, Suliman N.; Baldus, Marc; Weckhuysen, Bert M.
Abstract: Methanol‐to‐olefin (MTO) catalysis is a very active field of research because there is a wide variety of sometimes conflicting mechanistic proposals. An example is the ongoing discussion on the initial C−C bond formation from methanol during the induction period of the MTO process. By employing a combination of solid‐state NMR spectroscopy with UV/Vis diffuse reflectance spectroscopy and mass spectrometry on an active H‐SAPO‐34 catalyst, we provide spectroscopic evidence for the formation of surface acetate and methyl acetate, as well as dimethoxymethane during the MTO process. As a consequence, new insights in the formation of the first C−C bond are provided, suggesting a direct mechanism may be operative, at least in the early stages of the MTO reaction.